CottonGVD: A Comprehensive Genomic Variation Database for Cultivated Cottons - Peng, Zhen; Li, Hongge; Sun, Gaofei; Dai, Panhong; Geng, Xiaoli; Wang, Xiao; Zhang, Xiaomeng; Wang, Zhengzhen; Jia, Yinhua; Pan, Zhaoe; Chen, Baojun; Du, Xiongming; et al. (Frontiers in Plant Science, 2021)
Cultivated cottons are the most important economic crop produce natural fiber for textile industry. In recent years, the genetic basis of several essential traits for cultivated cottons has been gradually elucidated by decoding their genomic variations. Although an abundance of resequencing data is available in public, there is still lack of a comprehensive tool to exhibit the results of genomic variations and genome wide association study (GWAS). To assist cotton researchers in utilizing these data efficiently and conveniently, we constructed the cotton genomic variation database (CottonGVD: http://120.78.174.209/ or http://db.cngb.org/cottonGVD). This database contains the published genomic information of three cultivated cotton species, the corresponding population variations (SNP and InDel markers), and the visualized results of GWAS for major traits. The various built-in genomic tools help users retrieve, browse, and query variations conveniently. The database also provides interactive maps (such as Manhattan map, Scatter plot, Heatmap, and Linkage disequilibrium block) to exhibit GWAS and expression GWAS (eGWAS) results. Cotton researchers could easily focus on phenotype-associated loci they are interested in and screen for candidate genes. Moreover, CottonGVD will continue update by adding more data and functions.